Integration of population genetics with oceanographic models reveals strong connectivity among coral reefs across Seychelles - Burt, AJ; Vogt-Vincent, N; Johnson, H; Sendell-Price, A; Kelly, S; Clegg, SM; Head, C; Bunbury, N; Fleischer-Dogley, F; Jeremie, M-M; Khan, N; Baxter, R; et al. (Springer Nature, 2024)
Many countries with tropical reef systems face hard choices preserving coral reefs in the face of climate change on limited budgets. One approach to maximising regional reef resilience is targeting management efforts and resources at reefs that export large numbers of larvae to other reefs. However, this requires reef connectivity to be quantified. To map coral connectivity in the Seychelles reef system we carried out a population genomic study of the Porites lutea species complex using 241 sequenced colonies from multiple islands. To identify oceanographic drivers of this connectivity and quantify variability, we further used a 2 km resolution regional ocean simulation coupled with a larval dispersal model to predict the flow of coral larvae between reef sites. Patterns of admixture and gene flow are broadly supported by model predictions, but the realised connectivity is greater than that predicted from model simulations. Both methods detected a biogeographic dispersal barrier between the Inner and Outer Islands of Seychelles. However, this barrier is permeable and substantial larval transport is possible across Seychelles, particularly for one of two putative species found in our genomic study. The broad agreement between predicted connectivity and observed genetic patterns supports the use of such larval dispersal simulations in reef system management in Seychelles and the wider region.